Telefones celulares: Influência nos sistemas auditivo e vestibular - Balbani, Aracy Pereira Silveira [UNESP]; Montovani, Jair Cortez [UNESP] (Elsevier, 2008)
Telecommunications systems emit radiofrequency, which is an invisible electromagnetic radiation. Mobile phones operate with microwaves (450900 MHz in the analog service, and 1,82,2 GHz in the digital service) very close to the user's ear. The skin, inner ear, cochlear nerve and the temporal lobe surface absorb the radiofrequency energy. Aim: literature review on the influence of cellular phones on hearing and balance. Study design: systematic review. Methods: We reviewed papers on the influence of mobile phones on auditory and vestibular systems from Lilacs and Medline databases, published from 2000 to 2005, and also materials available in the Internet. Results: Studies concerning mobile phone radiation and risk of developing an acoustic neuroma have controversial results. Some authors did not see evidences of a higher risk of tumor development in mobile phone users, while others report that usage of analog cellular phones for ten or more years increase the risk of developing the tumor. Acute exposure to mobile phone microwaves do not influence the cochlear outer hair cells function in vivo and in vitro, the cochlear nerve electrical properties nor the vestibular system physiology in humans. Analog hearing aids are more susceptible to the electromagnetic interference caused by digital mobile phones. Conclusion: there is no evidence of cochleovestibular lesion caused by cellular phones. © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Mobile phones: Influence on auditory and vestibular systems
Keywords: Cellular phone; Hearing; Microwaves; Radio waves